2022
DOI: 10.1038/s41598-022-21671-w
|View full text |Cite
|
Sign up to set email alerts
|

Tracking blobs in the turbulent edge plasma of a tokamak fusion device

Abstract: The analysis of turbulence in plasmas is fundamental in fusion research. Despite extensive progress in theoretical modeling in the past 15 years, we still lack a complete and consistent understanding of turbulence in magnetic confinement devices, such as tokamaks. Experimental studies are challenging due to the diverse processes that drive the high-speed dynamics of turbulent phenomena. This work presents a novel application of motion tracking to identify and track turbulent filaments in fusion plasmas, called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…We then applied a machine learning-based blob tracking algorithm [28] to high-resolution GPI videos in order to directly observe the impact of RF-induced radially-sheared poloidal flows on blob propagation in the SOL. We have shown that these radially sheared flows can slow down, stretch, and destroy the radially moving blobs.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We then applied a machine learning-based blob tracking algorithm [28] to high-resolution GPI videos in order to directly observe the impact of RF-induced radially-sheared poloidal flows on blob propagation in the SOL. We have shown that these radially sheared flows can slow down, stretch, and destroy the radially moving blobs.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…To study the interaction of these E × B flows with SOL filaments, we apply a newly developed machine learning-based blob tracking algorithm [28] to the GPI data from the two discharges over a time window of 47 ms. Of the four baseline methods implemented, we choose to use the RAFT model, as it was shown to perform best in [28]. In total, the algorithm detects 780 blobs in the case without ICRF and 942 blobs in the case with ICRF.…”
Section: Direct Observation Of Blob Shearing By Rf-induced Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern recognition and tracking from images is a wellknown task in ML, and has been implemented for blobtracking in GPI data [17]. Four benchmarked models were trained with synthetic GPI data and two of the models show excellent performance on real GPI data, both in shape prediction and blob regime identification.…”
Section: Model For Blob-tracking In Gpi Imagesmentioning
confidence: 99%
“…In particular, the contribution of blobs of different sizes to the cross-field particle transport is investigated, as they belong to different turbulent regimes depending on their sizes [7,15]. To obtain the distribution of blob sizes, we use gas puff imaging (GPI) data with our newly developed machine learning (ML) model for blob-tracking [16,17], which tracks the shapes and trajectories of individual blobs frame-by-frame. We used the ML blob-tracking to estimate the cross-field particle transport, assuming that the light emission in the GPI data corresponds to the radial convective motion, and that the far-SOL transport is essentially convective, not diffusive [18].…”
Section: Introductionmentioning
confidence: 99%